KAJIAN BAHAN BAKAR HSD, MFO, LNG TERHADAP BIAYA DAN DAYA LISTRIK YANG DIHASILKAN DI PLTG PEMARON - Satria Abdi Wicaksana, Putu; Maharta Pemayun, Anak Agung Gede; Setiawan, I Nyoman (Jurnal SPEKTRUM; Vol 10 No 1 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i01.p9, 2023)
With the increasing demand for electrical energy, steps are needed to increase the production of electrical energy and one of them is the study of PLTG fuel. The PLTG fuel study aims to analyze the ratio of the generated electric power and fuel costs to the power generated by the PLTG. The benefit of this study is to know how much the ratio of power and fuel costs to the power produced, so that it can be used as a reference to determine which fuel is suitable for use. With a quantitative descriptive analysis method where the qualitative data from the calculation results will be described descriptively so that the advantages, disadvantages and differences of the three fuels can be identified. Through SFC calculations the results of this study show that LNG fuel has the lowest SFC value of 0.13 kg/kWh while for HSD it is 0.33 kg/kWh and MFO is 0.43 kg/kWh. With the same amount of fuel, the power produced by LNG is still higher than the other two fuels, which is 40.48 kWh, followed by HSD, which is 25.77 kWh, and MFO, which is 22.63 kWh. When viewed from an economic perspective, LNG is also the cheapest fuel, with a price of IDR 33,639.02, -, while MFO is slightly cheaper than HSD, which is IDR 194,000.00 and for HSD fuel, which is IDR 223,500.00,-.